Nanopartículas de CeO2 modificadas com Er obtidas pelo método hidrotermal microondas: estudo fotoluminescente - Cataldi, Guilherme de Almeida Merlo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of nanostructured materials have aroused great interest of the industries all over the country, since they enable the development of devices that can be used as gate insulators on silicon transistors, electrochromic devices, solid electrolyte oxygen sensors and as a photoluminescent materials . In this project, it is proposed to investigate the optical properties of CeO2 modified with rare earth Er processed in hydrothermal-microwave. The synthesis of one-dimensional nanostructures (1D) was measured from dilute aqueous solutions of acids and salts of starting reagents in the presence of chemical basis, after these aqueous solutions were processed on hydrothermal-microwave to particle growth. The particles obtained after processing were characterized by X-ray Diffraction, Rietveld Analysis and Raman Spectroscopy. The particle morphology was observed by scanning electron microscopy with field emission gun. The synthesis of 1D nanostructures are evaluated for different surfactants and starting precursors (ceria different salts), pH, temperature and pressure which can modify the morphology of the nanostructures. Combining laboratory experiments and theoretical calculations it was desired to understand the organization of the nanoparticles and their resulting structure. Strict control of chemical homogeneity, crystal structure, microstructure and interaction of the CeO2 cluster with different surfactants using the Hartree-Fock method, was intended to obtain properties compatible with their use in catalysts and optical devices. The use of mineralizer agent KOH and 8 minutes of processing time synthesis conditions were chosen to evaluate the effect of Er dopant. It has been proved that this doping with rare earth increases the photoluminescent properties of the compound obtained without change the structural and morphological propreties of ceria

O desenvolvimento de materiais nanoestruturados tem despertado grande interesse das indústrias em todo país, uma vez que estes possibilitam o desenvolvimento de dispositivos que podem ser usados como isolantes de porta em transistores de silício, dispositivos eletrocrômicos, eletrólitos sólidos em sensores de oxigênio e como materiais fotoluminescentes. Neste projeto, propõe-se investigar as propriedades ópticas do CeO2 modificado com a terra rara Er processados em hidrotermal-microondas. As sínteses das nanoestruturas unidimensionais (1D) foram realizadas a partir das soluções aquosas diluídas dos sais e ácidos dos reagentes de partida em presença de bases química, depois estas soluções aquosas foram processadas em hidrotermal-microondas para crescimento das partículas. As partículas obtidas após processamento foram caracterizadas por difração de raios X, análise de Rietveld e espectroscopia Raman. A morfologia das partículas foi observada por microscopia eletrônica de varredura com canhão de elétrons por emissão de campo. A síntese das nanoestruturas 1D foram avaliadas para diferentes surfactantes e precursores de partida (diferentes sais de céria), pH, temperatura e pressão que podem variar as morfologias das nanoestruturas. Combinando-se experimentos de laboratório e cálculos teóricos desejou-se entender a organização das nanopartículas e sua estrutura resultante. Um rigoroso controle da homogeneidade química, estrutura cristalina, microestrutura e interação do cluster de CeO2 com diferentes surfactantes usando o método de Hartree-Fock teve como finalidade a obtenção de propriedades compatíveis com seu uso em catalisadores e dispositivos ópticos. O uso do agente mineralizador KOH e o tempo de processamento de 8 minutos foram as condições de síntese escolhidas para a avaliação ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Nanopartículas; Fotoluminescencia; Microscopia eletronica de varredura; Nanoparticles